Forehand and Backhand Tennis Exercises: Study Literature Review - Jatra, Rices; Alnedral; Firdaus, Kamal (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. The sport of tennis is one of the most popular branches globally and there are various techniques in hitting tennis. The purpose of this article review is to find out about exercises to improve groundstroke ability in tennis in Indonesia. The research method uses a literature review (Study Literature Review). Materials and methods. The article selection model is often carried out using the prism flow diagram method. As many as 20 National Journal articles used as references in writing. Results. Based on the results of the analysis of the data obtained, it states that footwork and tennis court drills can improve the ability of groundstroke forheand and backhand accuracy in court tennis. This research can be categorized as having a very high success rate. Conclusion. The conclusion of this study is that footwork exercises and tennis court drills can improve groundstroke accuracy forehand and backhand in the very good category, and are also supported by several exercises or other training methods.